1996
DOI: 10.1159/000289078
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Manifest Dream Content Associated with Migraine Headaches: A Study of the Dreams That Precede Nocturnal Migraines

Abstract: Background: Clinical observations of a relationship between unpleasant dreams and migraine headaches have been reported previously. Methods: Due to the anecdotal quality of these case reports, this study empirically investigated the significance of this relationship. Dream content categories were selected corresponding to emotional factors associated with stress that trigger migraine headaches. A total of 37 migraineurs recorded 10 dreams each, 5 that preceded migraines and 5 that did not. Results: Univariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 13 publications
1
22
0
3
Order By: Relevance
“…To elucidate this hypothesis, it would be very interesting to study persons with periodic pain, e.g., persons with migraine, and compare pain dream frequencies in pain-free intervals with pain dream frequencies during their attacks. Interestingly, the dreams before waking up with a migraine attack are characterized by more anger and aggressive interactions [31] compared to awakenings without migraine but pain dreams have never been studied in that population. It would also be very interesting to study the hypothesis that dreams can not only reflect pain experienced by the dreamer in his or her waking life but might also reflect situations in which the person has seen another person in pain in real-life or via media.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate this hypothesis, it would be very interesting to study persons with periodic pain, e.g., persons with migraine, and compare pain dream frequencies in pain-free intervals with pain dream frequencies during their attacks. Interestingly, the dreams before waking up with a migraine attack are characterized by more anger and aggressive interactions [31] compared to awakenings without migraine but pain dreams have never been studied in that population. It would also be very interesting to study the hypothesis that dreams can not only reflect pain experienced by the dreamer in his or her waking life but might also reflect situations in which the person has seen another person in pain in real-life or via media.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Vgontzas et al (35) reported that adults with migraine were more than four times as likely to report nightmares of childhood onset compared to those without migraine. Small clinical studies have suggested that dreams, especially those characterized by a strong negative effect, can sometimes predict attacks of migraine particularly those characterized by a strong negative effect (36, 37). …”
Section: Discussionmentioning
confidence: 99%
“…Single case studies [40] and a controlled group study [41] demonstrated a relationship between negatively toned dream content and migraine attacks upon awakening. This relationship might again be explained, though, by the daytime stressors that were elicited in these studies.…”
Section: Discussionmentioning
confidence: 99%